Insights into sympathetic nervous system and GPCR interplay in fetal programming of hypertension: a bridge for new pharmacological strategies. Issue 4 (April 2020) - Vieira-Rocha, Maria S.; Sousa, Joana B.; Rodriguez-Rodriguez, Pilar; Morato, Manuela; Arribas, Silvia M.; Diniz, Carmen
Highlights: Fetal programming of hypertension (FPH) increases cardiovascular diseases statistics. Excessive sympathetic activation is a relevant factor in FPH. Expression and functional changes of G-protein-coupled receptors (GPCR) in FPH. Interaction between sympathetic nervous system and GPCRs in FPH. GPCR-based therapeutics are crucial to prevent and/or treat FPH. Abstract : Cardiovascular diseases (CVDs) are the most common cause of death from noncommunicable diseases worldwide. In addition to the classical CVD risk factors related to lifestyle and/or genetic background, exposure to an adverse intrauterine environment compromises fetal development leading to low birth weight and increasing offspring susceptibility to develop CVDs later in life, particularly hypertension – a process known as fetal programming of hypertension (FPH). In FPH animal models, permanent alterations have been detected in gene expression, in the structure and function of heart and blood vessels, compromising cardiovascular physiology and favoring hypertension development. This review focuses on the role of the sympathetic nervous system and its interplay with G-protein-coupled receptors, emphasizing strategies that envisage the prevention and/or treatment of FPH through interventions in early life.